PENGARUH PEMASARAN PRODUK PERSONAL CARE PRIA KAHF MELALUI INTERNAL DAN EXTERNAL SOCIAL INFLUENCER TERHADAP MINAT PEMBELIAN DENGAN BRAND AWARENESS SEBAGAI VARIABEL INTERVENING DI KOTA SEMARANG - Daffa Muhammad Naufal; Susilo Toto Rahardjo (Diponegoro Journal of Management, 2022)
The global men's personal care market will measure USD 30.8 billion in 2021 and is expected to grow at a compound annual growth rate (CAGR) of 9.1% from 2022 to 2030. Responding to today's men's skin and facial care needs, PT Paragon Technology and Innovation continues to innovate by launching its newest product, Kahf. A men's personal care brand with new advancements that are relevant to today's needs introduces a range of skin and body care products that are halal, premium, and natural. In addition to this phenomenon, based on the existing literature, shows that there is a research gap where previous research on social influence marketing only discussed external social influencers and rarely discussed internal social influencers. So based on the phenomena and gaps in this research, this is the basis for this research. This study aims to develop a conceptual model of internal social influencers and external social influencers in influencing purchase intention by using brand awareness as an intermediary. The next problem in this research is how to use the variables in the Theory of Reasoned Action (TRA) to increase buyer interest. The sample used in this study amounted to 174 residents domiciled in Semarang City with an age range of 15-34 years who have watched/seen marketing campaigns from the Kahf brand, both in the form of online and offline campaigns. This research method uses Structural Equation Model (SEM) analysis with AMOS as a data processing tool. Based on the results of the study, it was found that internal social influencers, external social influencers, and brand awareness had a positive and significant effect on consumer buying interest. Therefore, all hypotheses in this study were accepted. This study also proves that brand awareness is able to mediate the relationship between internal and external social influencers on buying interest. So it is hoped that this research can be useful in developing the marketing strategy of PT. Paragon Technology and Innovation. and can be a valuable literature for the benefit of academics.